An Investigation into the Internationalisation Strategy of Knowledge Intensive Businesses – A Case Study of Simitri Group, Singapore - Ray, Kerry (2010)
This dissertation examines the internationalisation of small knowledge intensive businesses. This area of study is currently relatively under researched with the majority of internationalisation literature focusing on large manufacturing multinationals. Knowledge intensive businesses have numerous unique characteristics that differentiate them from other companies that significantly impact their internationalisation strategies and success. This was illustrated through the case study of Simitri Group, a small management and training consultancy headquartered in Singapore that was explored through several of Ghemawat’s global strategy frameworks. The main characteristics that were found to influence their internationalisation were their reliance on idiosyncratic knowledge, the influence of networks and the characteristics of human knowledge. In addition several themes emerged outside of the framework that were directly linked to the small size of the company emerged throughout the study, most importantly the contradiction between the large demands from the company’s multinational clients and their resource limitations and the importance of coincidence on their internationalisation strategy. Overall the study found that whilst KIBS companies share some of the characteristics of standard service firms and large KIBS companies, and Ghemawat’s frameworks can explain the case study’s internationalisation pattern to an extent however they cannot sufficiently explain all the unique characteristics of the growing industry of small intensive businesses.